Inflation and Economic Growth in the Philippines - Josef T. Yap (Philippine Institute for Development Studies (PIDS), 1996)
Analysis of pertinent data shows that Krugman's warning about the serious repercussions of a number of disinflation methods is relevant for the Philippine case. While financial managers have correctly responded during the crisis years, policy responses during the recovery phases from 1986-1995 have been myopic. Analysis also indicates that prevention of real effective exchange rate given volatile capital flows requires interest targeting from the Central Bank.
Keywords: 330; economic recovery; inflation; economic growth